Association between lymphocyte subsets and cytomegalovirus infection status among patients with systemic lupus erythematosus: A pilot study. Issue 39 (September 2019) - Qin, Ling; Qiu, Zhifeng; Hsieh, Evelyn; Geng, Taoran; Zhao, Jiuliang; Zeng, Xiaofeng; Wan, Lu; Xie, Jing; Ramendra, Rayoun; Routy, Jean Pierre; Li, Taisheng
Abstract : Abstract: This study aimed to determine the association between different lymphocyte subsets and cytomegalovirus (CMV) infection status in patients with systemic lupus erythematosus (SLE). We performed a retrospective study among SLE patients with CMV infection and collected patient socio-demographic and clinical characteristics, as well as their recorded circulating lymphocyte subsets. Univariate and multivariable logistic regression analyses examined the relationship between CMV infection status and lymphocyte subset counts. We included 125 hospitalized patients with SLE, consisting of 88 with documented CMV infection and 37 without any evidence of CMV or other infections. Among the 88 CMV-infected patients, 65 (73.8%) patients developed CMV disease and 23 (26.2%) presented as CMV viremia. Compared to uninfected patients (1520 ± 101 cells/μL), lymphocytes remained stable among those with CMV viremia (1305 ± 272 cells/μL, P = .995). However, compared to their uninfected counterparts, there was a marked decrease in lymphocytes among patients with CMV disease (680 ± 513 cells/μL, P < .001). Analysis of lymphocyte subsets via flow cytometry showed that CD4+ T cell, CD8+ T cell, and natural killer cell counts were lower among those with CMV disease compared to those with CMV viremia and those without infection. Further, multivariable analysis showed that total lymphocyte (odds ratio [OR] 0.999, 95% confidence interval [CI] 0.998–1.000, P = .007) and CD4+ T cell counts (OR 0.99, 95% CI 0.992–0.998, P = .003) were negatively associated with CMV disease. Our findings support a potential inverse relationship between lymphopenia, specifically CD4+ T-cell lymphopenia, and CMV disease among hospitalized SLE patients.